غنی پروازءُ ناگمانءِ آزمانکانی دیم پہ دیمی وانشت: Comparative Studies of short Stories of Ghani Parwaz and Naguman - Rafiq, Muhammad; Baloch, Dr.Hamid Ali (Hanken, 2020)
Ghani Parvaz and Nágumán are the prominent short story writers in the Balochi literature, who wrote on the different issues of the Baloch society, using the same themes, but in different styles. The writing style, the usage of language, especially the usage of idioms, a good plot and a good climax makes the short stories of Naguman stronger than the short stories of Ghani Parvaz. This paper discusses the writing styles, the usage of language, the plot and climax of both short story writers and finds out the writing style differences between them.